Planning of Soybean Raw Material Inventory Control Using Economic Order Quantity (EOQ) Method, in Corina Factory Kudus, Central Java - By, Syajidha Einjelica; Yamit, Zulian (Universitas Negeri Semarang, 2022)
This research aims to determine the results of inventory planning carried out by the company and by using the EOQ (Economic Order Quantity) method. The data obtained is based on the records made by the researcher to the Corina factory for a period of 3 years in 2019 -2021 . The data used in this study are: sales data, production data, purchase data of soybean raw materials, raw material inventory data, soybean raw material ordering cost data, raw material storage cost data. The analysis was carried out using the EOQ formula, safety stock, reorder point. Soybean raw materials carried out by the Corina factory is considered less effective because there is an excess of available raw materials compared to their use for a period of 3 years, while the control of raw materials according to EOQ (Economic Order Quantity) is considered more efficient and optimal. . It is proven that there is a decrease in inventory costs (order costs and storage costs) of Rp. 25,315,412 with a purchase frequency of 4 times a year. Meanwhile, the raw material control carried out by the Corina factory before using the Economic Order Quantity (EOQ) method was Rp. 31,675,608 for ordering costs and Rp 428,640 for holding costs , so the total inventory cost before using the Economic Order Quantity (EOQ) method was Rp 32,104. 248.